Financial Feasibility and Sensitivity of Arabica Coffee Farming In Simalungun District, Sumatra Utara Province - Yuliarti, Ellys; Muhamad Mustopa Romdhon; Saragih, Luciana (Journal of Agri Socio Economics and Business, 2023)
Arabica coffee productivity in Simalungun Regency has the highest value, namely 1.25 tons/ha, among other arabica coffee producing districts in Sumatra Utara Province. However, the level of feasibility of return on investment made by farmers of arabica coffee has not been measured. The research method used to determine the feasibility and sensitivity of arabica coffee farming is Net B/C ratio, Gross B/C ratio, Profitability Ratio, Net Present Value and Internal Rate of Return. The results of the research show that arabica coffee farming is financially feasible based on the criteria of Net B/C Ratio (2.33), Gross B/C Ratio (1.38), Profitability Ratio (2.31), NPV (Rp. 23,194,329), and IRR (25.06%). The sensitivity of arabica coffee farming occurs if fertilizer and labor costs increase by 55% and production prices fall, then arabica coffee farming is not worth pursuing. Arabica coffee farming in Raya Huluan Village is financially feasible but farmers have not been able to independently cultivate arabica coffee properly. Therefore, farmers are given assistance on how to cultivate arabica coffee farming, types of fertilizer and dosage of fertilizer, timing of fertilizer application so that the economic life of arabica coffee is more than 10 years.